Reduction of Driveline Infections Through Doubled Driveline Tunneling of Left Ventricular Assist Devices. Issue 1 (11th January 2013) - Fleissner, Felix; Avsar, Murat; Malehsa, Doris; Strueber, Martin; Haverich, Axel; Schmitto, Jan D.
Abstract The durability of ventricular assist device (VAD) therapy improved steadily over the past years. However, driveline infections remain a challenge. To test whether an improved surgical implantation technique may lower the incidence of infections, we analyzed all patients receiving a VAD implantation in the years 2008 and 2009 (group 1) and compared them with all patients who received a VAD in 2011 (group 2) after we changed our implantation method. The new technique involves tunneling of the driveline into the fascia of the musculus rectus abdominis, resulting in a longer, intrafascial run to achieve a better resistance against ascending infections. We retrospectively analyzed 40 patients in group 1 and 41 patients in group 2. One year after implantation, the infection rate was markedly reduced (22.5% [n = 9] group 1 vs. 4.9% [n = 2] group 2, P < 0.001) by the new implantation method. There was, however, no significant improvement in overall mortality. The Cox regression model identified the implantation method as an independent risk factor for 1 year after implantation driveline infection (P < 0.05). In conclusion, the new tunneling technique marks a great leap forward in long‐term VAD treatment. However, overall mortality remains high and needs further improvement.